Sociodemographic Factors Related to Lower Urinary Tract Symptoms in Men: A Korean Community Health Survey - Jo, Jung Ki; Kim, Kyu Shik; Nam, Ji Won; Choi, Bo Yul; Moon, Hong Sang (International neurourology journal, 2017)
This study estimated the prevalence of lower urinary tract symptoms (LUTS) in Korean men and the conditions for being diagnosed with or treated for LUTS/benign prostatic hyperplasia (BPH). We analyzed cross-sectional data collected from 69,851 Korean men who were 40 years of age or older and had participated in the Korean Community Health Survey performed in 2011. Interviewers performed face-to-face surveys that included sociodemographic questions, the International Prostate Symptom Score (IPSS), and questions regarding whether the subjects had been diagnosed with or treated for LUTS/BPH. We estimated the prevalence of LUTS and assessed whether the subjects had been diagnosed with or treated for LUTS/BPH. Moderate to severe LUTS, storage symptoms, and voiding symptoms increased with age. The IPSS quality of life score was 1.5±0.004 in the mild LUTS group (n=57,701), 3.3±0.01 in the moderate LUTS group (n=9,203), and 4.3±0.02 in the severe LUTS group (n=2,947) (P<0.0001). The prevalence of moderate to severe LUTS in those who had not been diagnosed with LUTS/BPH was 64.5% (7,847 of 12,150), and the prevalence of moderate to severe LUTS in those who had been diagnosed with LUTS/BPH but had not been treated was 23.5% (2,853 of 12,150). The severity of LUTS in Korean men increased with age, and the IPSS quality of life score increased with the severity of LUTS. Many Korean men with moderate to severe LUTS had not been diagnosed or treated for LUTS/BPH. Socioeconomic conditions played an important role in health-seeking behavior among patients with LUTS/BPH.